Role of social capital on flood resilience capacity: Evidence analysis from Susta, Nawalparasi Paschim, Nepal - Gyawali, N.; Devkota, D.; Chaudhary, P.; Chhetri, A.; Devkota, N. R. (Journal of Agriculture and Forestry University, 2020)
Social capital is the interaction and inter, or intra relationship among family, community, and external groups. There are three types of social capital: bonding, bridging, and linking to enhance flood resilience and make the communities better prepared. Flood resilience is the coping capacity of the community to prepare, respond, and recover from a flood shock, or stressor. A study was done to understand the role of social capital on flood resilience in the two communities i.e. Kudiya and Paklihawa of Susta municipality of Nawalparasi Paschim. Accordingly, household survey, Focus Group Discussion (FGD), and Key Informants Interview (KII) were carried out to collect the qualitative and quantitative data and information. The analysis of the data and information shows that among the three social capitals, bonding and bridging social capitals are quite strong in the communities, but linking social capital is weaker. 94% of the 402 respondents reported to have engagement with other community members, or groups whereas 91% respondents reported that they have stronger community to community coordination, and 67% respondents opined that they do not have access to external resources. The linking social capital needs to be strengthened to enhance flood response capacity of the two communities. It means that local government should work closely with local communities as per their needs and requirement and leverage the funds to the communities.